Kinetic Studies of Hydrodesulfurization of Vacuum Distillate - A.K.Mohammed, Abdul-Halim; A.K, Abdul-Monaem; A.A., Hiadar (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Vacuum gas oil (611-833)K was distilled from Kirkuk crude oil, which was obtained by blending the following fraction, light vacuum gas oil (611 - 650) K, medium vacuum gas oil (650-690)K, heavy vacuum gas oil (690-727)K and very heavy vacuum gas oil (727-833)K. The vacuum gas oil was hydrotreated on a commercial cobalt-molybdenum alumina catalyst presulfied at specified condition in a laboratory trickle bed reactor. The reaction temperature varied from (583-643)K over liquid hourly space velocity ranging between (1.5-3.75)h-1 , Hydrogen pressure was kept constant at 3.5 MPa with a hydrogen to oil ratio of about 250 L/L The conversion results for desulfurization appeared to obey the second order kinetics. According to this model rate constants for desulfurization reaction were calculated. Finally, the apparent activation energy (Ea), enthalpy of activation ( H*) and entropy (  S*) were calculated based on the values of rate constant (k). The calculated values of Ea, H* and  S* were 74.657 kJ/mole, 74.712 kJ/mole and 167.132 J/mole.k, respectively.